Pengaruh Karakteristik Rumah Tangga, Keragaman Makanan, Lingkungan Hidup terhadap Status Gizi Balita - Rahmawati, Fitria Nur; Mulyaningsih, Tri; Daerobi, Akhmad (Media Kesehatan Masyarakat Indonesia, 2019)
The household or family is a place for children to maximize their growth and development and fulfill their nutrition, to create high-quality human resources and to drive the country’s economic growth for the future. This study aims to examine factors of household socioeconomic characteristics, dietary diversity, and the environment and their effects on the nutritional status of children under five in Indonesia. This study uses cross-sectional design and uses secondary data from Indonesia Family Live Survey (IFLS) wave 5 (IFLS5). IFLS is a longitudinal survey of a random sample of 83% of the population in Indonesia in 1993. The sample in this study was children aged 0-60 months (toddlers), totaling 4,670 children under five. The research method is to use a multinomial logistic regression model. The results showed that the nutritional status of children under five years old was affected by family income, mother’s education, the gender of children under five, residential areas, access to drinking water and good sanitation. The conclusion is that the mother’s education has a significant influence on the three nutritional status of children under five, namely wasted, severely wasted, and overweight.